Choosing the best testing tools to increase project productivity start preventing errors throughout the software development life cycle. - Kolawa, Dr. Adam
The primary mission of information technology is to improve business processes and increase profits. Companies are constantly rethinking and struggling with how to use IT to a competitive advantage, reduce IT operating and maintenance costs, and reduce the total cost of ownership...all while attempting to deliver increased value.